Enhanced Anti-cancer Potency Using a Combination of Oleanolic Acid and Maslinic Acid to Control Treatment Resistance in Breast Cancer - Cigir Biray Avcı; Fatma Sogutlu; Neslihan Pinar Ozates; Behrouz Shademan; Cumhur Gunduz (Tabriz University of Medical Sciences, 2023)
Purpose: The phosphatidylinositol 3-kinase/AKT/mammalian target of rapamycin (PI3K/AKT/ mTOR) pathway is a complex intracellular metabolic pathway that leads to cell growth and tumor proliferation and plays a key role in drug resistance in breast cancer. Therefore, the anti-cancer effects of oleanolic acid (OA), maslinic acid (MA), and their combination were investigated to improve the performance of the treatment strategy. Methods: We investigated the effect of OA and MA on cell viability using the WST-1 method. The synergistic effect of the combination was analyzed by isobologram analysis. In addition, the effects of the two compounds, individually and in combination, on apoptosis, autophagy, and the cell cycle were investigated in MCF7 cells. In addition, changes in the expression of PI3K/AKT/mTOR genes involved in apoptosis, cell cycle and metabolism were determined by quantitative RT-PCR. Results: MA, OA, and a combination of both caused G0/G1 arrest. Apoptosis also increased in all treated groups. The autophagosomal LC3-II formation was induced 1.74-fold in the MA-treated group and 3.25-fold in the MA-OA-treated group. The combination treatment resulted in increased expression of genes such as GSK3B, PTEN, CDKN1B and FOXO3 and decreased expression of IGF1, PRKCB and AKT3 genes. Conclusion: The results showed that the combination of these two substances showed the highest synergistic effect at the lowest dose and using MA-OA caused cancer cells to undergo apoptosis. The use of combination drugs may reduce the resistance of cancer cells to treatment.